Developing Strategies to Avoid Post-Expo Slump for Sustainable Urban Planning in Dubai - Tachouali, Dania (2016)
In recent years, mega-events have been popular catalysts for urban sustainability; they have magnificent impacts on the host city from (environmental, physical, social and economic) aspects; in 2020 Dubai will be hosting Expo which is considered the third largest global event in terms of economic and cultural impact during its six month run, this study mainly discussed how can EXPO sustain the success of EXPO after the end of the event, many scholars generally addressed the preparation for the event without considering the legacy phase, the research identified difficulties in achieving sustainability are very similar to issues associated with assessing the impacts of mega events through the time cycle of EXPO, therefore, the research aimed to fill this gap by creating strategies that help in sustaining the success of Expo 2020; these strategies can be used by Expo stakeholders to utilize the infrastructure of Expo 2020 for Dubai’s long term sustainable planning needs and objectives especially the urban planners. The research evaluated four international case studies to show the planning behavior of each ex-host city, the lessons learnt from these previous experiences will help in demonstrating the relationship between sustainable urban planning and hosting Expo to achieve a sustainable World EXPO. The research found that the success of EXPO can be sustained by contributing EXPO in the urban sustainable development of the host city; therefore, the research identified EXPO’s role from sustainable urban aspect. As Dubai is still in the preparation phase the research covered the pre-event level from sustainable urban planning aspect, and extracted lessons from Shanghai which hosted EXPO 2010 with a sustainability related theme, Shanghai was a significant example to follow on how to achieve a good urbanism; with regards to Shanghai EXPO 2010, the research suggested guidelines for Dubai EXPO 2020 to follow based on the sustainable world EXPO strategies and a legacy plan to avoid post-EXPO slump.